Gentiles of the Soul: Maximus the Confessor on the Substructure and Transformation of Human Passions - Blowers, Paul M. (Journal of early Christian studies, 1996)
Maximus the Confessor, in his attempt to deal with the problems of human passion, freedom, and love in an ontological and physiological as well as moral framework, is seen by some scholars to be adumbrating the thought of Aquinas on these subjects. Yet the argument here is that Maximus's doctrine of the human passions is aimed not per se at a comprehensive metaphysics of human passibility or at a doctrine of supernaturally infused [inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="01i"/], but—still very much in a neo-Cappadocian (and to some degree neo-Areopagitic) key—at a teleology of the passions that judges their ultimate ontological status in relation to the latent chaotic element in bodily nature, the definition of the frontiers of human freedom, and the ongoing, ever-unfolding potentiality, resourcefulness, and moral-spiritual "utility" of all natural human faculties. All of this belongs, moreover, within Maximus's larger Christological perspective. As the "gentiles" of the soul, to use Maximus's own analogy, the passions are a "contingent presence" in the history of human nature, and despite their deviance in connection with the abuse of free will, they still constitute a crucial vehicle by which incarnational grace is embodied in the farthest reaches of the cosmic order, of which human nature is the treasured microcosm.